WEB QUESTING IN TEFL COURSES: WHAT FACTORS DETER THE STUDENTS’ INFORMATION-SEEKING BEHAVIOR? - Маджид Фарахян; Фаршад Пархамнія; Мілад Шейхбаної (Інформаційні технології і засоби навчання, 2021)
The survival and the continuity of an organization’s operations depend upon the use of information. As such, investigating the Webquesting behavior of university students in general and TEFL (Teaching English as a foreign language) students in particular during the Covid 19 seems essential. Since information-seeking behavior can be influenced by various factors we aimed to explore the attitude of TEFL students  towards webquesting. In the next phase of the study, we sought the barriers to TEFL students’ Webquesting behaviour. Accordingly, the present research employed both qualitative and quantitative approaches. The statistical population consisted of 128 TEFL students and the sampling method was purposeful. The findings of this study revealed that the students were not satisfied with their webquesting and that there were two major obstacles in their webquesting, namely, learners’ constraints and teachers’ constraints. The inhibitors included lack of familiarity with Internet sources, poor information seeking skills, lack of interest in some topics, lack of skills in using the Internet, poor English proficiency, teachers’ lack of CALL (computer assisted language learning) preparation, lack of help from the side of teachers, teachers’ lack of attention to non-textbook resources, and students’ lack of motivation and time. Findings have implications for TEFL teachers, since, based on the qualitative data, the most important source of information for students is textbooks and the most important goal of searching for information is for doing homework. The importance of textbooks for students is the result of the pivotal role given to the text books by teachers and the final exams.  Perhaps students’ lack of interest in webquesting is partly due to such an undue emphasis. On the other hand, students’ lack of interest in Webquesting was also due to the lack of attention and encouragement from the side of teachers to use the Internet resources.